The Role of D2-like Dopaminergic Receptor in Dopamine-mediated Modulation of Th17-cells in Multiple Sclerosis - Melnikov, Mikhail; Sviridova, Anastasiya; Rogovskii, Vladimir; Kudrin, Vladimir; Murugin, Vladimir; Boyko, Alexey; Pashenkov, Mikhail (Current Neuropharmacology, 2022)
Background: Dopamine is one of the main mediators capable regulate the neuroimmune interaction and is involved in multiple sclerosis (MS) pathogenesis. Objective: The aim of this study was to clarify the role of dopamine and its receptors in modulation of Th17-cells in MS. Methods: 34 relapsing-remitting MS patients and 23 healthy subjects were examined. To assess the effect of dopamine on Th17-cells, CD4+ T-cells were cultured in the presence of dopamine and antagonist or agonist of D1- or D2-like dopaminergic receptors and stimulated with anti-CD3/CD28- microbeads. The levels of cytokines in supernatants were assessed by ELISA. Results: Production of interleukin-17 (IL-17), interferon-γ (IFN-γ), granulocyte-colony stimulating factor (GM-CSF), and IL-21 by CD4+ T-cells as well as dopamine were comparable between the groups. Dopamine suppressed cytokine secretion by activated СD4+ T-cells in both groups. Blockade of D1-like dopaminergic receptor with a specific antagonist SCH23390 did not affect dopaminemediated cytokine suppression. In contrast, blockade of D2-like dopaminergic receptor by sulpiride decreased dopamine's inhibitory effect on IL-17 secretion in both groups and GM-CSF and IL-21 production in MS patients. Blockade of D1-like dopaminergic receptor directly inhibited IL-17, IFN- γ, GM-CSF in both groups and IL-21 production in healthy subjects, while blockade of D2-like dopaminergic receptor had no effect on cytokine secretion. Finally, activation of D2-like dopaminergic receptor with a specific agonist quinpirole decreased cytokine production in both groups. Conclusion: These data suggest an inhibitory role of dopamine on Th17-cells in MS, which could be mediated by the activation of the D2-like dopaminergic receptor.
Keywords: neuroimmunology